Age/disease duration influence on activities of daily living and quality of life after levodopa-carbidopa intestinal gel in Parkinson's disease. (10th April 2018) - Antonini, Angelo; Robieson, Weining Z; Bergmann, Lars; Yegin, Ashley; Poewe, Werner
Aim: To determine if age and Parkinson's disease duration at therapy initiation influence the efficacy of levodopa-carbidopa intestinal gel (LCIG) on quality of life and activities of daily living.Patients & methods: This post hoc analysis assessed subgroups of patients stratified by baseline age, disease duration, hours/day of 'off' time and levodopa equivalent dose. Patients' data were collected from the GLORIA study, a 24-month observational registry evaluating long-term effectiveness of LCIG.Results & conclusion: LCIG therapy led to sustained improvements in quality of life irrespective of patient age and disease duration at baseline. Improvements in activities of daily living were observed across all subgroups, particularly in younger patients, patients with shorter disease duration and in patients with the highest baseline levodopa equivalent dose.